Studies on the comparative radiosensitivity of susceptible and Cyanox resistant strains of pink bollworm Pectinophora gossypiella (Saund.) (Bollettino di zoologia agraria e bachicoltura, 2024)
When susceptible and Cyanox resistant pink bollworm (Pectinophora gossypiella Saund.) pupae were irradiated at dose levels ranging from 50 to 500 Gy, fecundity and mating ability of the adults were greatly affected. The susceptible strain was more affected by radiation, and females were more radiosensitive. Mating ability of irradiated males of both strains did not significantly decreased at doses up to 300 Gy, however, mating ability of irradiated females was significantly reduced than irradiated males at doses of 200 Gy and above. Irradiated females of both strains had a tendency to mate with unirradiated males more often than unirradiated females with irradiated males. Moths of both strains showed a high correlation between the increasing of the dose and the number of depositing eggs or the percent of hatching. A dose of 200 Gy sterilized most (96.06%) males and all females of susceptible strain, while a dose of 300 Gy induced complete sterility for resistant females and 91.4% of sterility of their respective males.
Keywords: Pectinophora gossypiella; radiation; Cyanox; susceptibility; resistant; strains